PENGARUH STRES KERJA TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI - Sutarno, Supriyatun, Alwi Suddin & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2018)
This study aims to determine the effect of significance between: 1) JobStress toward Employee Performance, 2) Job Stress toward EmployeeSatisfaction, (3) Job Satisfaction toward Employee Performance, 4) JobSatisfaction as mediating the influence of work stress toward employeeperformance of Bank Mandiri Branch Madiun. Population of 64 people.Samples taken on census Technique of data collection through validity andreliability test. Data analysis techniques use multiple linear regression andclassical assumption test. Hypothesis testing with Path Analysis, t test, sobeltest, F test and . The result of regrestion 1, obtained t test value equal to5,737 < 0,05, Test F equal to 32,915 < 0,05 coefficient of determination ( )= 34,7%. Result of regrestion 2, obtained value of Test of t equal to 2,910,5,835 < 0,05, Test of F obtained value 47.849 < 0,05 which means jobsatisfaction have an effect on signifikan to employee performance.Coefficient of determination 61,1%. The ratio of indirect effect 0,339, totalinfluence 0,627 and result of value score test get value of Z equal to 4,1014 >1,96 so it can be concluded that job satisfaction is able to mediate theinfluence of work stress toward employee performance of Bank MandiriBranch Madiun. Conclusion of result of hypothesis stated that "there issignificant effect of work stress on performance, there is significant influenceof job stress to job satisfaction, there is significant influence of satisfaction onperformance and job satisfaction able to mediate influence of work stresstoward employee performance of Bank Mandiri Branch Madiun" tested thetruth.Keywords: Job stress, work satisfaction, performance.